BIRTH WEIGHT PERCENTILES BY GESTATIONAL AGE: A HOSPITAL BASED STUDY - PARVEEN, ZAHIDA (Journal of Ayub Medical College Abbottabad, 2001)
Background: There are no present or old large population based birth weight nomograms available for Pakistani Population The aim of the study was to develop birth weight for gestational age nomogram for singleton and twin births. based on perinatal data collected prospectively. Methods: Until weight percentiles by gestational age were determined in women delivering at Agha Khan University Hospital Karachi from January 1992 to December 1994. This was a prospective cohort Study and included all women "lie delivered from 28 weeks to 44 weeks of gestation Singleton as well as twin pregnancies were included but women having intrauterine or intrapartum deaths were excluded Results: Data of 1041 live births were collected from 4041 deliveries. Total infants were 4112, there being 71 sets of twins The male babies were heavier than female babies at each gestational week There was a preponderance of male infant's tor each week Out of 4041 deliveries, 414 babies were born before 37 completed weeks; percentage of preterm birth is 10.24%. Males were more likely to be born preterm (hen were females, although females were more likely to be of low birth weight. Out of 414 preterm births. 281 were male and 183 were female Out of them data of 4030 live births was compiled and analysed; percentiles were formed and compared with other studies.